On (ɱ,ɳ)-Strongly Fully Stably Banach Algebra Modules Related to an Ideal of Am ×ɳ - Radhi Ibraheem Mohammed Ali; Muna Jasim Mohammed Ali; Samira Naji Kadhim (مجلة بغداد للعلوم)
The aim of this paper is introducing the concept of (ɱ,ɳ) strong full stability B-Algebra-module related to an ideal. Some properties of (ɱ,ɳ)- strong full stability B-Algebra-module related to an ideal have been studied and another characterizations have been given. The relationship of (ɱ,ɳ) strong full stability B-Algebra-module related to an ideal that states,  a B- -module Ӽ is (ɱ,ɳ)- strong full stability B-Algebra-module related to an ideal  , if and only if  for any two ɱ-element sub-sets and of Ӽɳ, if , for each j = 1, …, ɱ,  i = 1,…, ɳ  and   implies Ạɳ( ) Ạɳ(  have been proved..